Policy Evaluation on International Research Quality Management of Universitas Indonesia: Impact Towards Development of the Nation - Sari, Rini Ambar; Matin, Matin; Akbar, Maruf (ASEAN Journal of Community Engagement, 2023)
Despite the significant role of higher education research and innovation, the quality management of such aspects in our local universities can be further transformed and better integrated with national development. This research identifies the many challenges regarding quality research management faced by many universities in Indonesia, particularly related to research and innovation. In response to such challenges, the study exhibits a comprehensive evaluation of the formulation and performance of university research policy plans and programs, examining the critical impact of Universitas Indonesia’s (UI) performance of its research policy and strategic plan. The result indicates that the performance of UI’s global research quality management policy has shown optimized, efficient, and effective outcomes. The policy has impacted Indonesia’s science, technology, and social development in line with the strategic plan, quality management, and good university governance. This study may inform higher education management on synergizing research policy and programs within the organization’s strategic plan toward global science and technology competitiveness in higher education.